Analysis of MTs Students' Critical Thinking Skills in Solving Algebra Problems Based on Facione's Theory - Siska Nisaul Alawiyah; Sudirman Sudirman; Slamet Slamet (PRISMA, 2026)
This study aims to analyze the critical thinking skills of Madrasah Tsanawiyah (MTs) students in solving algebraic problems based on Facione’s critical thinking theory. Critical thinking is an essential competence in mathematics learning, particularly in algebra, which requires students to interpret problems, apply appropriate strategies, and draw logical conclusions. This research employed a qualitative descriptive approach to explore students’ cognitive processes in depth. The study was conducted in one eighth-grade class of an MTs in Kediri Regency, involving 25 students. Purposive sampling was used to select research subjects representing high, medium, and low critical thinking ability categories. Data were collected through algebra problem-solving tests and in-depth interviews, which were validated by experts prior to implementation. The analysis followed the Miles and Huberman qualitative analysis model, including data reduction, data display, and conclusion drawing, with method triangulation to ensure data validity. The results showed that only two students (8%) were categorized as having high critical thinking skills, fifteen students (60%) were in the medium category, and eight students (32%) were in the low category. Students with high critical thinking skills fulfilled all Facione indicators, while students in the medium and low categories showed difficulties, particularly in the analysis, evaluation, and inference aspects. These findings indicate that students are not yet accustomed to higher-order thinking skills (HOTS) algebra problems and highlight the need for learning strategies that consistently train critical thinking in mathematics classrooms. Keywords: algebra; critical thinking; Facione’s theory; MTs students; problem solving